2016
DOI: 10.1136/annrheumdis-2015-209020
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating levels of interferon-γ and interferon-γ-induced chemokines characterise patients with macrophage activation syndrome complicating systemic juvenile idiopathic arthritis

Abstract: The high levels of IFNγ and of IFNγ-induced chemokines and their correlation with the severity of laboratory abnormalities of MAS suggest a pivotal role of IFNγ in MAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(190 citation statements)
references
References 38 publications
13
166
1
3
Order By: Relevance
“…IFNγ levels were found to be higher in patients with active MAS at sampling compared to patients with active sJIA without MAS at sampling [41]. Using the above mentioned mouse model of MAS in IL-6 transgenic mice we have also found that neutralization of IFNγ improved survival and reverted biochemical abnormalities (Prencipe G. 2016 submitted).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFNγ levels were found to be higher in patients with active MAS at sampling compared to patients with active sJIA without MAS at sampling [41]. Using the above mentioned mouse model of MAS in IL-6 transgenic mice we have also found that neutralization of IFNγ improved survival and reverted biochemical abnormalities (Prencipe G. 2016 submitted).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL9 is known to be specifically induced by IFNγ [42]. Indeed in patients with active MAS levels of IFNγ and CXCL9 were strictly related to laboratory features of MAS, including ferritin levels, white blood cell and platelet counts, and LDH [41]. These correlations were not present in patients with active sJIA without MAS.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the cytokine storm reflected in plasma of patients with inherited HLH and MAS has been indistinguishable (elevated CXCL9/IFN-g, TNF-a, sIL-2Ra, IL-1, and IL-6). 6,7 Differentiating MAS from HLH is further confounded by recent observations of up to 40% of patients with MAS having monoallelic mutations in the common HLH-associated cytotoxicityregulating genes 8 (with uncertain impact of genetic dosage on pathogenesis). There is a clear need to understand the specific lesions in immune regulatory pathways that underlie unbridled inflammation in critically ill patients with MAS and HLH to facilitate diagnosis and optimize therapy.…”
Section: Texasmentioning
confidence: 99%
“…We did not make any changes in the sJIA classification in this study except for the two patients who were re-categorized to "unclassified arthritis" due to the presence of anti-CCP Ab. sJIA is characterized by prominent systemic features, marked activation of the innate immune system, and important pathogenic roles played by interleukin 1 (IL-1), IL-6, and interferon-γ [12,40]. Adult-onset Still's disease is considered similar to sJIA, but the former is different in terms of arthritis not being an essential diagnostic criterion [12].…”
Section: Discussionmentioning
confidence: 99%